Production of in vitro strawberry (Fragaria × ananassa) plantlets in large-scale system supplemented with silver nanoparticles - Thuong, Tran Thi; Tung, Hoang Thanh; Khai, Hoang Dac; Hien, Vu Thi; Luan, Vu Quoc; Cuong, Do Manh; Nam, Nguyen Ba; Chau, Nguyen Hoai; Vinh, Bui Van The; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2021)
The growth of strawberry plantlets in the rooting stage on culture medium supplemented with silver nanoparticles (AgNPs) and the ethylene gas accumulation in plantlet culture bottles were investigated. In addition, different culture systems were first used to produce large-scale Strawberry plantlets. The results showed that shoots (3 cm) were cultured on MS medium supplemented with 0.02 mg/L NAA, 1 g/L activated charcoal, 30 g/L sucrose, 8 g/L agar and 0.5 mg/L AgNPs showed about 4 days earlier rooting formation and the plantlet growth such as plantlet height (5.60 cm), fresh weight (242.67 mg), dry weight (34,67 mg), number of roots/plantlet (6.67), root length (3.40 cm), SPAD (39.30 nmol/cm2) were higher than those in the control after 15 days of culture. Besides, the ethylene gas content in the culture bottle (0.06 ppm) in the 0.5 mg/L AgNPs treatment was lower than as compared to that in the control (0.15 ppm) after 15 days of culture. A shoot density (10 shoots) in 250 mL culture bottle with 40 mL of medium gave optimal growth than those in other treatments after 15 days of culture. Square plastic box culture system (length × width × height: 19 cm × 19 cm × 7 cm; 2.5 L in volume) containing 250 mL MS medium added to 0.5 mg/L AgNPs produced 100 vigorous plantlets; meanwhile, rectangular plastic box system (34 cm × 23 cm × 13 cm; 10 L in volume; 10 L in volume) produced 200 vigorous plantlets. Plantlets derived from 0.5 mg/L AgNPs treatment in the plastic box systems exhibited well acclimatization after 30 and 60 days of culture in the greenhouse.